A pocket full of kisses - Penn, Audrey, 1947-; Gibson, Barbara (Washington, D.C. : Scholastic, 2004)
Chester Raccoon is worried that his mother does not have enough love for both him and his new baby brother.
AD 830
Accelerated Reader
Accelerated Reader AR
Keywords: Mother and child -- Juvenile fiction; Sibling rivalry -- Juvenile fiction; Romance fiction -- Juvenile literature; Infants -- Juvenile fiction; Raccoon -- Juvenile fiction; Romance fiction